Study of ion dynamics in lanthanum aluminate probed by conductivity spectroscopy - Verma O.N.; Singh N.K.; Raghvendra; Singh P. (My University, 2025)
Ion conducting lanthanum aluminate, LaAlO3 was synthesized via a citrate nitrate auto combustion route. Phase formation of LaAlO3 was studied by thermal and powder X-ray diffraction techniques. The conductivity spectra of LaAlO3 were investigated in the frequency range 20 Hz to 1 MHz at different temperatures. The conductivity data were analyzed in terms of Jonscher's power law. The dc conductivity and hopping frequency of the charge carrier were extracted from the analysis of conductivity spectra. The corresponding value of activation energy implies that the conductivity is mainly dependent on the mobility of the charge carriers. The conductivity spectra were scaled according to Ghosh scaling. Moreover, the modulus spectra were also scaled. Both the scaling behaviours reflected the temperature independent conduction mechanism in the system. © 2015 The Royal Society of Chemistry.